Astronomical references in Chaucer - Kennedy, Victor (ELOPE (Ljubljana), 2005)
One of the problems in the field of English literature studies is that, with compartmentalization and specialization, it becomes introspective to the point where it devolves into the study of metafiction and metacriticism. At its heart, however, literature has to be about something: Thackeray claimed its subject is human nature, but human nature is based in the interface between human and nature. This paper explores some of the problems in the interface between human knowledge, institutions, and nature, and will offer an example of cross-disciplinary, historical study to illustrate a well-known but, to most modern readers, impenetrable medieval text, Chaucer's Treatise on the Astrolabe. It ends with three recommendations: look to history, cross boundaries between academic fields, and use practical, as well as theoretical, teaching methods.
Keywords: angleška književnost; astrolab; astrologija; astronomija; Chaucer, Geoffrey; srednjeveška književnost